Trends of Neonatal Mortality in context of Case Overload in Al - Alwyia Pediatric Teaching Hospital at Baghdad during 2005-2012 - Raham, Tareef Fadhil; Abood, Assad Muhsen (AL-Kindy College Medical Journal, 2016)
Background: Data on the impact of neonatal and total pediatric admissions volume on neonatal mortality are sparse. Objectives: This study is done to estimate the neonatal mortality in relation to neonatal admissions and to total hospital admissions in Al-Alwyia Pediatric Teaching Hospital through years 2005-2012 Type of the study: A retrospective study.Methods: statistical records of all cases admitted to APTH were studied during 2005-2012.Results: Neonatal mortality decreased to the nadir at last year of study period (2012) and reached 6.1% of neonatal admissions compared to 2005 level which was 9.7 %. Mortality rate among premature and low birth weight (LBW) infants decreased also. The study also reveals that neonatal mortality constitute significant a contribution to childhood mortality (61.4 %) and morbidity (28.3%) throughout the study years. With a highly significant p value parallel to increasing number of neonatal admissions (case over load) , there is a trend of neonatal mortality rate to be decreased Case fatality rate also decreased among overall children to 3.5% in 2005 and to 3.3% in 2013 in spite of 2.4 times increase in neonatal admission during the study period.This neonatal overload is more than overall pediatric over load, because the total hospital admissions are increased just 1.2 times.Conclusions: The neonatal admissions case overload is high and increasing and constitutes a significant proportion of total childhood mortality. Neonatal mortality including premature and (LBW) infants is decreasing .Further actions are needed to meet global goals.